Research on the Targeted Treatment of Squamous Cell Carcinoma by Nanographene Drug Delivery System - Xiangyu Zhang; Liwei Guo; Zhenbang Sun; Deming Han; Lihui Zhao (Advances in Materials Science and Engineering)
In order to find an effective cure for squamous cell carcinoma, we innovatively used nano-graphene oxide as a pharmaceutical delivery system, overcoming resistance to cisplatin-targeted anti-squamous carcinoma. For this purpose, we prepared a nano-graphene oxide using an oxidation method, functionally modified with polyethylene glycol (PEG) and branched polyethyleneimine (BPEI) and loaded with the antitumor drug cisplatin (CDDP), a compound with preliminary anticancer efficacy. Then, anti-human squamous cell carcinoma monoclonal antibody was combined to construct a target graphene nanopharmaceutical system. The administration system was applied to nude mice carrying human squamous cell carcinoma. Through the detection of frozen tissue slices, the anti-squamous cell carcinoma effect and targeting of the graphene nanoloaded system were analyzed. The safety of the pharmaceutical system was confirmed through further experiments. Results showed that the NGO-PEG-BPEI-CDDP-Antibody complex had a significant antitumor effect and was able to enter the nude mice and targeted squamous cell carcinoma cell and effectively kill squamous cell carcinoma cells, thus reducing the use of clinical chemotherapeutic drugs, improving the efficacy and providing a new answer for the treatment of squamous cell carcinoma.